Bioprospecting of actinorhodin and undecyprodigiosin in mangrove streptomyces - Nur Azam bin Amirdun @ Amirudin (Kulliyyah of Science, International Islamic University Malaysia, 2019)
The family Streptomycetaceae, notably species in genus Streptomyces, have long been the subject of investigation due to their well-known ability to produce secondary metabolites. The emergence of drug resistant pathogens and the relative ease of producing genome sequences has renewed the importance of Streptomyces as producers of natural products and resulted in revived efforts in isolating and describing strains from novel environments. Even though thousands of secondary metabolites have been discovered from Streptomyces, less attention has been given in understanding the bioprospecting of the secondary metabolites in Streptomyces lived in mangrove ecosystem. Therefore, the current study was designed to investigate the production of secondary metabolites which were actinorhodin and undecylprodigiosin from mangrove Streptomyces which were grown in different parameters. A Streptomyces sp. k2-11 taken from Microbiology Laboratory, IIUM Kuantan campus have been successfully cultured in starch yeast agar (SYE) which used sea water as to mimic the mangrove environment. The Streptomyces sp. k2-11 had 99.62% similarity with Streptomyces prasinus strain NRRL B-12521. The phylogeny analysis shown that the Streptomyces sp. K2-11 had close relationship with Streptomyces coelicolor strain NBRC 12854. However, DNA-DNA relatedness and phenotypic data distinguished the strains which S. coelicolor known as primary source of actinorhodin and undecylprodigiosin production. This work revealed that actVI_orf6 sequence had 99.62% of sequence similarities with S.coelicolor gene actI_orf1, actI_orf2, actI_orf3, actVII, actIV and actVb encoded for beta-ketoacyl synthase/ acyl transferase, acyl carrier protein, cyclase/ dehydrase, dehydrase and dimerase, respectively. Conversely, redD sequence had as much as 98.83% similarities with S. coelicolor redD promoter region. High performance liquid chromatography (HPLC) of the extracted secondary metabolites detected the presence of actinorhodin and undecylprodigiosin compounds. Both compounds shown inhibitory activity to Bacillus subtilis and no activity against Streptococcus aureus in disc diffusion assay. Streptomyces sp. grown in SMMS media was recorded to be the highest (1.49 x108 cfu/ml) compared to SYE and R2 media. The production of antibiotics was tested on three different parameters which were incubation temperature, pH and glucose levels. Actinorhodin recorded high yield at 33°C of incubation temperature (1.95x10-6 mol/L), pH 5 (7.1x10-6 mol/L) and 50 % w/v glucose (9.56x10-6 mol/L) for 60 hours of incubation. On the other hand, production of undecylprodigiosin was recorded the highest at 37°C of incubation temperature for 5 hours of incubation (5.04x10-7 mol/L), pH 5 at 40 hours of incubation (6.24x10-7 mol/L) and in 75% w/v glucose at 40 hours of incubation (1.36x10-6 mol/L). The present findings suggested that mangrove Streptomyces sp. produced high yield of actinorhodin and undecylprodigiosin under extreme or stress condition.